2017
DOI: 10.1016/j.euromechsol.2016.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Application of empirical mode decomposition to drive-by bridge damage detection

Abstract: A new method is proposed in this paper for bridge damage detection using the response measured in a passing vehicle. It is shown theoretically that such a response includes three main components; vehicle frequency, bridge natural frequency and a vehicle speed pseudofrequency component. The Empirical Mode Decomposition (EMD) method is used to decompose the signal into its main components. A damage detection method is proposed using the Intrinsic Mode Functions (IMFs) corresponding to the vehicle speed component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(72 citation statements)
references
References 29 publications
1
71
0
Order By: Relevance
“…where θ = (EI) 1 /(EI) 2 , α = a/L, β = b/L and γ = c/L. Suppose L = 20 m, (EI) 1 = 3.33 × 10 9 Nm 2 , α = 0.5, β = 0.025, θ = 1.05, we can depict the distribution of k 0 /k in Figure 6a for different k according to Equations (9), (28), (30), and (32). It observes that the effective vehicle stiffness has an abrupt change at the damaged location, and this change is more sensitive to damage with larger k. This conforms with the conventional knowledge that stiffer vehicle is more sensitive to damage.…”
Section: The Deflection Of a Damaged Beam Under A Unit Point Loadmentioning
confidence: 99%
See 2 more Smart Citations
“…where θ = (EI) 1 /(EI) 2 , α = a/L, β = b/L and γ = c/L. Suppose L = 20 m, (EI) 1 = 3.33 × 10 9 Nm 2 , α = 0.5, β = 0.025, θ = 1.05, we can depict the distribution of k 0 /k in Figure 6a for different k according to Equations (9), (28), (30), and (32). It observes that the effective vehicle stiffness has an abrupt change at the damaged location, and this change is more sensitive to damage with larger k. This conforms with the conventional knowledge that stiffer vehicle is more sensitive to damage.…”
Section: The Deflection Of a Damaged Beam Under A Unit Point Loadmentioning
confidence: 99%
“…This idea was adopted in the work of OBrien and Malekjafarian . These authors also proposed to detect damage by intrinsic mode functions extracted from the vehicle responses …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et. al [20,21] proposed drive-by or indirect bridge monitoring, in which the bridge condition is evaluated using the response measured on a passing vehicle [22]. It is particularly promising for short and medium span bridges.…”
Section: Introductionmentioning
confidence: 99%
“…OBrien et al [9] use empirical mode decomposition (EMD) of the accelerations measured on a passing vehicle for damage detection. It is shown that some components of the signal include the damage information.…”
Section: Introductionmentioning
confidence: 99%